Pola Hubungan Rantai Makanan (Food Chain) antara Tipe Habitat dan Keanekaragaman Spesies Burung di Lahan Reklamasi dan Revegetasi Pasca Tambang Batu Bara - Sri Soegiharto (Jurnal Penelitian Ekosistem Dipterokarpa, 2020)
In the Natural succession is closely linked to occupation plant and animal. The occupation depending food chain between kind of plant and many of animal species animal. The aim of this research is to determine the food chain tipe each habitat, in hopes of being referenced in the recommendation of how to faster succession in recalamation area. Data were analyzed using hyper Cannonical Correspondence Analysis (hCCA) with data grouped into B1-n (bired species), S1-n (shrub species), F1-n (food chain), P1-n (plant production/edible food). The results of this study were founded 21 shrub species and 36 bird species. The potential of bird species distribution in the post-mining revegetation area is variated dipending many shrub species every area.